The Impact of Computer on the Deviant Behaviors Exhibition of Teenagers : A Case Study of Albania - Brahja, Eljana (European Scientific Journal, ESJ, 2017)
Technology is placing teenagers in front of diverse choices that the virtual world enables. The purpose of this study is to explain how technology affects relationships that teenagers have with other individuals in the real world. The study's research question is: Does the use of computers affect the exhibition of deviant behaviors among teenagers? The research method used for the findings of this study is the quantitative method. Data was collected using a questionnaire. The population of the study was 1,680 teenagers from Sander Prosi and Myslym Keta high schools located in Tirana, Albania. The sample selected according to the defined criteria for completing the questionnaires is 453 students from the 10th, 11th and 12th grade. Based on the Positive Paradigm, the quantitative research method will serve to recognize the reality. Research data is processed through the SPSS statistical method and the result with the Cronbach alpha validation coefficient, Î± = 0.852. Based on the Interactional Theory (Thornberry, 2015), it is aimed to shed light on the behavioral patterns exhibited by teenagers who are computer users. From the research findings, students who used computer to play, and not for scientific research, were more involved in deviant behavior. They were predisposed to conflict with friends, dim relationships with people surrounding them in the real world, dropping out of school, etc. To avoid such a situation, it is recommended to strengthen the cooperation in the real world amongst parents, students, and teachers.